Protective Effect of Pyxinol, One Active Ingredient of Lichenes on Cisplatin-Induced Nephrotoxicity via Ameliorating DNA Damage Response - Yang, Yanting; Zhu, Xiuhong; Yu, Guohua; Ma, Jinbo (Frontiers in Pharmacology, 2021)
Background: Cisplatin is a valuable chemotherapeutic agent against malignant tumors. However, the clinical use of cisplatin is limited by its side effects such as renal injury. Pyxinol is an active constituent of Lichenes and its effects on cisplatin-induced nephrotoxicity is currently unknown. This study aims to examine the potential protective effects of pyxinol on cisplatin-induced renal injury and explore the underlying mechanisms. Methods: In vivo rat model of cisplatin-induced nephrotoxicity was induced by intraperitoneal (i.p) administration of cisplatin. The blood urea nitrogen and creatinine levels were measured and renal histological analysis was conducted to evaluate the renal function; The TUNEL staining, western blotting and real-time PCR assays were conducted to examine related molecular changes. Finally, the in vivo anti-tumor efficacy was examined in the xenograft tumor model using nude mice. Results: Pretreatment with pyxinol attenuated cisplatin-induced increase in blood urea nitrogen, creatinine and urinary protein excretion and the magnitude of injury in the renal tubules. Pyxinol ameliorated the activation of p53 via attenuating the DNA damage response, which then attenuated the tubular cell apoptosis. Finally, pyxinol could potentiate the in vivo anti-tumor efficacy of cisplatin against the xenograft tumor of cervical cancer cells in nude mice. Conclusions: Combining pyxinol with cisplatin could alleviate cisplatin-induced renal injury without decreasing its therapeutic efficacy, which might represent a beneficial adjunct therapy for cisplatin-based chemotherapeutic regimens in the clinic.